SYNTHESIS AND APPLICATION OF ACRYLIC FILMS IN PAINT AND VARNISH MATERIALS - А.N. Nurlybayeva; E.I. Rustem; H.R. Sadiyevа; G.A. Seitbekova; A.S. Darmenbayeva; M.S. Kalmakhanova; А.М. Egisinova; U.T. Otinshieva (Academic Scientific Journal of Chemistry, 2020)
Copolymerizations of unsaturated compounds with different ratios of acrylic monomers were synthesized. The synthesized copolymers exhibit good adhesion, flexibility and waterproofing performance may be used in the paint industry. The behavior of the copolymers of MMA and BuMA and proven by IR spectroscopy. This paper describes the synthesis, structure and properties of certain block copolymers. The practical application of scanning electron microscopy used for investigation of materials